On Creation of Computational Infrastructure for Development of Science in Armenia. - Shoukourian, Yuri (Mathematical Problems of Computer Science, 2021)
The vital necessity of new research methods based on the usage of perspective computing resources, data collections and scientific tools (i. e. e-science) promises to assist to scientific inventions. Numerous advanced countries have accepted the direction of e-science, which gives high importance to the construction and development of e-infrastructures assisting it. An important part of e-science is the computational science [1, 2, 3] The Computational science is a rapidly growing multidisciplinary field that uses advanced computing capabilities to understand and solve complex problems. CS fuses three distinct elements [2]: numerical and non-numerical algorithms and modeling and simulation software developed to solve science (e.g., biological, physical, and social), engineering, and humanities problems; advanced system hardware, software, networking and data management components developed through computer and information science to solve computationally demanding problems; the computational infrastructure that supports both science and engineering problem solving and development of computer and information science.